The hidden kingdom - Beck, Ian (Oxford University Press, 2011)
A pampered prince who has to give up everything he has ever known. A warrior-like girl who has promised to carry out her duty at any cost. An obedient young servant with a mission to complete and an icy chill in his heart. As ancient demons rise around them and conspire to destroy their world, only these three people can defeat the evil which threatens to engulf them. -- pub. website.